Recommendations for Measurement of Attention Outcomes in Preschoolers With Neurofibromatosis. Issue 7 (17th August 2021) - Klein-Tasman, Bonita P.; Lee, Kristin; Thompson, Heather L.; Janusz, Jennifer; Payne, Jonathan M.; Pardej, Sara; de Blank, Peter; Kennedy, Tess; Janke, Kelly M.; Castillo, Allison del; Walsh, Karin S.
Abstract : Children with neurofibromatosis type 1 (NF1) are at increased risk for attention problems. While most research has been conducted with school-aged cohorts, preschool-aged children offer a novel developmental window for clinical studies, with the promise that treatments implemented earlier in the developmental trajectory may most effectively modify risk for later difficulties. Designing research studies around the youngest children with NF1 can result in intervention earlier in the developmental cascade associated with NF1 gene abnormalities. Furthermore, clinical trials for medications targeting physical and psychological aspects of NF1 often include individuals spanning a wide age range, including preschool-aged children. In a prior report, the REiNS Neurocognitive Subcommittee made recommendations regarding performance-based and observer-rated measures of attention for use in clinical trials and highlighted the need for separate consideration of assessment methods for young children. The observer-rated Attention-Deficit/Hyperactivity Disorder Rating Scale–Preschool version is recommended as a primary outcome measure. The NIH Toolbox Flanker, Dimensional Change Card Sort, and List Sort Working Memory tasks and Digits Forward from the Differential Ability Scales–2nd Edition (performance-based measures) are recommended as secondary outcome measures. Specific methodologic recommendations for inclusion of preschoolers in clinical trials research are also offered.